Healthy Eating: No-Cook Recipes - Jennifer Hillan; Emily Minton (EDIS)
Try these quick, easy recipes for balanced, healthy meals. No cooking required! This revised 2-page fact sheet was written by Jennifer Hillan and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, May 2012.